Pedagang Bugis dan kuasa Eropah di Selat Melaka, 1500-1800 - Nordin Hussin (Universiti Kebangsaan Malaysia, 2008)
There is few writings on the activities and role of Bugis traders and their skills and their significance in the Malay waters, despite the fact that their role in the Malay World has been noted by European travelers. This shortage of literature on Bugis traders is due to the limited historical sources of local literature on the subject. Most of the local sources were based on the reports made by European travelers and the record entries of ships in the ports of Melaka and Penang. These problems must not underestimate the significant contribution by the Bugis traders. This should be construed as a challenge to historians to embark on further historical research on the Bugis traders. This article will attempt to evaluate and analyse the important role of Bugis traders in Southeast Asia based on archival materials and travelogues. The article will also analyse the concept of self preservation among the Bugis in relation to their cultural heritage